Contrastive Analysis of Verbs Seen from Time in Arabic and Madurese - Arini Salsabila; Mokhammad Miftakhul Huda; Bambang Irawan (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research is motivated by the contrast between verbs in terms of time in Arabic and Madurese which can cause misunderstandings and difficulties in learning Arabic. The aim of this research is to examine aspects of similarities and differences in the verb structure of the two languages by comparing Madurese and Arabic by focusing on verb forms in terms of time between the two languages. This research uses a descriptive qualitative research method, which is included in the type of library research ( literature) and the researcher also observes naturally from daily conversations used by Madurese speakers, where data collection is limited to verbs that indicate time information. The result of this finding is that there is a contrast between Arabic and Madurese, both of which have different verb systems. In Arabic, verbs already contain time information which must follow the very consistent rules of the science of nahwu and its shorf. Meanwhile, in Madurese there is no time in the verb system, but the language has its own way of indicating time information in certain events. Even though the two languages have different ways of indicating the time of events, they also have similarities and similarities in the division of time.